Hypoxia in multiple sclerosis - Burtscher, Johannes; Motl, Robert W.; Berek, Klaus; Ehrenreich, Hannelore; Kopp, Martin; Hohenauer, Erich (Redox Biology, 2025)
Low oxygen availability (hypoxia) is a prominent but poorly understood feature in multiple sclerosis (MS). Whether hypoxia causes or drives MS pathology and symptoms or whether it is a consequence of other pathological events, such as inflammation and vascular dysfunction, is unknown. Here, we summarize the available literature on the interplay between hypoxia and both pathological and symptomatic features of MS. Severe environmental hypoxia (i.e., altitude) may trigger or facilitate MS-related events, possibly by exacerbating tissue hypoxia in the central nervous system. Accordingly, increasing oxygen supply can mitigate pathological and clinical parameters in MS models. In contrast, stimulating the endogenous hypoxia response and adaptation systems by controlled exposure to hypoxia (hypoxia conditioning) renders the central nervous system more resistant to hypoxic insults, thereby attenuating pathology and symptomatology in MS models. Overlapping mechanisms likely play a role in the benefits conferred by physical activity in MS. We provide an integrative model to explain the paradoxically beneficial outcomes of both increased and decreased ambient oxygen conditions. In conclusion, controlled exposure to hypoxia, perhaps in combination with exercise, is a promising, possibly disease-course modifying therapeutic approach for MS. However, many open questions remain.
Gesehen am 04.11.2025